The Projection Model As an Early Warning of Food Price Commodity Fluctuation - Pujiati, A; Oktavilia, S; Damayanti, N (KnE Social Sciences, 2018)
The price of food commodities are very significant to be analyzed because, apart from depicting the interaction between supply and demand, it also one of the most important elements of the economy of food resilience. Food price analysis is used to formulate the policy of price stabilization and product enhancement. This research aims to make observation and to technically analyze toward price fluctuation of some food commodities in Semarang city using ARIMA (Autoregressive Moving Average) Model analysis tool. ARIMA Model in this research is used to predict food price in short period of time, as well as an early warning detection of food price fluctuation. This research uses daily time series data in the span of 2015 to 2018. The source of the data is Commodity Price and Production Information System (SIHATI) Central Java Province, a publicized price survey. The research result shows that ARIMA Model that has been generated can predict price of some food commodities (i.e chicken meat, eggs, red chili peppers and shallots) in Semarang city. Keywords: projection model, price, price commodity, ARIMA